Dermoscopy of Keratinizing Skin Tumors: Cutaneous Squamous Cell Carcinoma, Keratoacanthoma, and Bowen’s Disease - Traini, Daniele Omar; Palmisano, Gerardo; Di Stefani, Alessandro; Longo, Caterina; Cappilli, Simone; Suppa, Mariano; Peris, Ketty (Dermatology Practical & Conceptual, 2026)
Introduction: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer, with incidence rising due to increased ultraviolet exposure, an aging population, and a growing number of immunocompromised individuals. Objectives: This review presents a comprehensive analysis of dermoscopic features of cSCC lesions, delineating distinct patterns of Bowen’s disease (BD) and invasive cSCC, including keratoacanthoma (KA). The primary outcome was the identification of dermoscopic patterns specific to cSCC, while the secondary endpoint involved determining the prevalence of these features across different subtypes. Methods: We selected studies including individuals with histopathologically proven cSCC who underwent dermoscopic evaluation. Studies with at least five cases of cSCC were included, with no constraint on the study design. Results: Our analysis reveals that BD typically exhibits white-to-yellow scales and glomerular vessels, whereas KA is characterized by a layered architecture with a central keratin plug, an ivory-white peripheral zone, and a symmetrical distribution of hairpin vessels. In contrast, invasive cSCC demonstrates a progression from well-differentiated lesions with organized vascular patterns to poorly differentiated forms marked by chaotic, polymorphic vessels and predominant red hues. Conclusion: These distinct dermoscopic patterns serve as practical clinical guides for differentiating SCC grades of invasion and differentiation, thereby enhancing diagnostic accuracy and patient management.